THE ROAD TO CULTURALLY RELEVANT PEDAGOGY: EXPATRIATE TEACHERS’ PEDAGOGICAL PRACTICES IN THE CULTURAL CONTEXT OF SAUDI ARABIAN HIGHER EDUCATION - Hamdan, Amani K (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2014)
This case study explored the need for culturally relevant pedagogy (CRP) in Saudi Arabian higher education, especially when students have a cultural background that differs from that of their instructor. The study documented how expatriate teachers structured their pedagogical practices in the Saudi Arabian context. It examined how these university teachers attempted to proactively accommodate students’ needs, prior experiences and performance, and how they promoted academic progress while teaching in a different culture. Six themes were revealed: (1) the challenges of constructivism in the Saudi Arabian context; (2) linking pedagogy to the lives of Saudi students; (3) alternating and adjusting teaching to address student needs; (4) connecting with students; (5) discrepancies in teachers’ beliefs; and (6) teachers’ assumptions and expectations about knowledge It is argued that CRP offers opportunities for better learning experiences for Saudi students. Through CRP, learning can be made more meaningful and can help in the development of a positive student identity. Some pedagogical strategies are offered to help teachers implement CRP. VERS UNE PÉDAGOGIE CULTURELLEMENT ADAPTÉE : LES PRATIQUES PÉDAGOGIQUES D’ENSEIGNANTS EXPATRIÉS ET À L’ENSEIGNEMENT SUPÉRIEUR DANS LE CONTEXTE CULTUREL DE L’ARABIE SAOUDITE Cet article examine les besoins en termes de pédagogie culturellement adaptée au niveau de l’enseignement supérieur en Arabie Saoudite et cible particulièrement les étudiants possédant un profil culturel différent de celui de leur enseignant. Cette étude présente comment les enseignants expatriés déploient leurs pratiques pédagogiques en Arabie Saoudite. Celle-ci analyse de quelle manière proactive les enseignants essaient d’accommoder les besoins, les expériences et les réalisations préalables des étudiants et comment ils encouragent les progrès scolaires tout en enseignant dans une culture différente. Six thèmes sont explorés: (1) relever les défis du constructivisme dans le contexte de l’Arabie Saoudite; (2) arrimer la pédagogie au vécu des étudiants saoudiens; (3) effectuer une alternance ou un ajustement de l’enseignement pour rencontrer les besoins des étudiants; (4) établir des liens avec les étudiants; (5) les divergences entre les croyances des enseignants et (6) les hypothèses et attentes des enseignants relativement au savoir. Dans cet article, l’auteur avance que la pédagogie culturellement adaptée offre de meilleures opportunités d’apprentissages aux étudiants saoudiens. Grâce à la pédagogie culturellement adaptée, l’apprentissage peut devenir plus pertinent et faciliter le développement d’une identité culturelle positive chez l’étudiant. Quelques pistes pédagogiques sont présentées pour aider les enseignants à utiliser ce type de pédagogie.